Answer
y = (1/4)x - 5 or 4y - x + 20 = 0
Explanation
To get the rule required, we interpret the sentence and write it in a mathematical form.
5 less than one fourth of x is y
one fourth of x ⇒ (1/4)x
5 less than one fourth of x is y ⇒ (1/4)x - 5 = y
y = (1/4)x - 5
4y = x - 20
4y - x + 20 = 0
Answer: Expression I & Expression II
Step-by-step explanation:
2n+n+3n+5 simplifies to 6n+5
The chosen topic is not meant for use with this type of problem. Try the examples below.
[-1,9)u(2,10]
(−1,2)∪(−4,0)
(−1,29)∪(26,50)